Temperature time evolution of the Assynt Terrane of the Lewisian Gneiss Complex of Northwest Scotland from zircon U-Pb dating and Ti thermometry - CROWLEY, QUENTIN (My University, 2015)
The Lewisian Gneiss Complex of Northwest Scotland is a classic Precambrian basement gneiss complex. The Lewisian is divided into a number of terranes on the basis of structural, metamorphic and geochronological evidence. The most well-studied of these is the Assynt Terrane, which forms the central part of the Lewisian outcrop on the Scottish mainland. Field evidence shows that it has a complex tectonothermal history, the early stages of which remain poorly constrained. This paper sets out to better understand the chronology and thermal evolution of the Assynt Terrane through zircon U-Pb dating and Ti-in-zircon thermometry, the latter applied to the Lewisian for the first time. This is placed in context by integration with detailed field mapping, sample petrography, zircon cathodoluminescence (CL) imaging and rare earth element (REE) analysis. Zircons from six tonalite-trondhjemite-granodiorite (TTG) gneiss samples and two metasedimentary gneiss samples were analysed. The TTG gneisses were predominantly retrogressed to amphibolite-facies; zircons showed a range of CL zoning patterns and REE profiles were similar to those expected for magmatic zircon grains. Zircons from the metasedimentary gneisses also displayed a range of CL zoning patterns and are depleted relative to chondrite in heavy REEs due to the presence of garnet. Zircon analysis records a spread of concordant U-Pb ages from ∼2500 to 3000 Ma. There is no evident correlation of ages with location in the crystal or with CL zoning pattern. A weighted average of 207Pb/206Pb ages from the oldest igneous zircon cores from the TTG gneiss samples gives an age of 2958 ± 7 Ma, interpreted to be a magmatic protolith crystallisation age. A weighted average of 207Pb/206Pb ages of the youngest metamorphic rims yields an age of 2482 ± 6 Ma, interpreted to represent the last high-grade metamorphism to affect these rocks. Ti-in-zircon thermometry records minimum temperatures of 710–834 °C, interpreted to reflect magmatic crystallisation. REE profiling enabled the zircons in the metasedimentary rocks to be linked to the presence of metamorphic garnet, but resetting of U-Pb systematics precluded the determination of either protolith or metamorphic ages. Zircons from the metasedimentary gneisses generally record higher minimum temperatures (803–847 °C) than the TTG gneisses, interpreted to record zircon crystallisation in an unknown protolith.
PUBLISHED
Keywords: Lewisian Gneiss Complex; Assynt Terrane; Zircon; U-Th-Pb; Ti-in-zircon thermometry; Smart & Sustainable Planet; Earth Science